Autophagy and cathepsin L are involved in the antinociceptive effect of DMBC in a mouse acetic acid-writhing model - Gu Wei-wei; Ao Gui-zhen; Zhu Yong-ming; Sun Shi-chang; Zhou Qiang; Fan Jia-hong; Nobuhiko Katunuma; Ishidoh Kazumi; Zhang Hui-ling; Gao Xiu-mei (Acta Pharmacologica Sinica, 2016)
Aim: 2-(3′,5′-Dimethoxybenzylidene) cyclopentanone (DMBC) is a novel synthetic compound with antinociceptive activities. The aim of this study was to investigate the roles of the autophagic-lysosomal pathway in the antinociceptive effect of DMBC in a mouse acetic acid-writhing model. Methods: Mouse acetic acid-writhing test and hotplate test were used to assess the antinociceptive effects of DMBC, 3-MA (autophagy inhibitor) and Clik148 (cathepsin L inhibitor). The drugs were administered peripherally (ip) or centrally (icv). Results: Peripheral administration of 3-MA (7.5–30 mg/kg) or Clik148 (10–80 mg/kg) produced potent antinociceptive effect in acetic acid-writhing test. Central administration of 3-MA or Clik148 (12.5–50 nmol/L) produced comparable antinociceptive effect in acetic acid-writhing test. Peripheral administration of DMBC (25–50 mg/kg) produced potent antinociceptive effects in both acetic acidwrithing and hotplate tests. Furthermore, the antinociceptive effect produced by peripheral administration of DMBC (50 mg/kg) in acetic acid-writhing test was antagonized by low doses of 3-MA (3.75 mg/kg) or Clik148 (20 mg/kg) peripherally administered, but was not affected by 3-MA or Clik148 (25 nmol/L) centrally administered. Conclusion: Activation of central autophagy and cathepsin L is involved in nociception in mice, whereas peripheral autophagy and cathepsin L contributes, at least in part, to the antinociceptive effect of DMBC in mice.